ANALISIS PEMBANGKIT LISTRIK TENAGA MIKRO HIDRO (PLTMH) DI DESA ARGAMUKTI KECAMATAN ARGAPURA KABUPATEN MAJALENGKA - perly Sumirat (PROCEEDING STIMA)
Majalengka Regency is located at the foot of Ciremai Mountain, where there are many waterfalls such as Muara Jaya Waterfall in Argamukti Village, Argapura District. The potential of this waterfall cannot be utilized further, only new to the utilization for the tourist area. Another possible utilization is the creation of Micro Hydro Power Plant (MHPP), which will be an efficient alternative energy solution because it only utilizes the available water drops. In writing this Job Training Report discussed on maintenance of Micro Hydro Power Plant, the influence of the nozzle valve openings to turbine rotation, the effect of turbine rotation to the voltage generated by the generator, generator rotation for the resulting voltage stable on 220-240V. Turbine velocity value of the largest of the test conducted is at 414.2 rpm, while the lowest is at 210.5 rpm. The turbine spinning test is subjected to a nozzle valve opening position. The result of the effect of the turbine rotation on the voltage generator, when the speed increases then the voltage will increase so vice versa. The effect of the generator spin on the generator voltage is the weaker the generator the weaker the voltage generated and vice versa.